Les appartenances ethnoculturelles en contexte scolaire à Maurice : auto-identification des futurs enseignants, perception de la diversité des élèves et conception d’une citoyenneté commune - Dimitri Cauchie (Recherches en Éducation)
This paper presents some of the outcomes of our doctoral research dedicated to the promotion of ethnocultural diversity within the Mauritian school. Following a brief literature review about the different community identities in Mauritius, we present results concerning the ethnic and cultural self-identification of the future primary school teachers, their intentions to take into account the diversity of their public school in their professional practices, and their conceptions of a common Mauritian identity. These results show a dynamic and evolving complexity of identities. The multiplicity of community affiliations is not denied but they do not plan to take into account the ethnocultural characteristics of their pupils. The exclusion of this factor seems to be the fair way of an equal school education and the development of a common identity is conceived as a citizenship not referring to religious affiliations. The Mauritian multiculturalism seems to be reinforced by the educational action of teachers and the intercultural development remains a challenge.